Learning English is Fun with Aarons English's Instagram Account - Racha Hafiez Sururi; Nurul Hasanah Fajaria (ELITE JOURNAL, 2023)
In the 5.0 era, we can learn through social media, one of it is Instagram. Through Instagram students are able to use social media to learn anything, including English. There are many sources and materials as well as tutors who can help students to learn like Aaron O'Brien's Instagram account (@aarons.english). This is a qualitative study with descriptive method. Observation and interview were used to find students' opinions of Aaron English's Instagram account. The sixth semester students of English Education at As-syafi'iyah Islamic University Jakarta who are following @aaron.english become participants of this study. The result shown that they like @aaron.english as a medium for learning English since it has a good and fun way presented in every video. Based on the findings of the interview above, it can be concluded that students enjoy watching content from Aaron English's Instagram account. Further, it can help students improve their English knowledge. After watching the videos, they believe that English learning materials are easy to understand and help them in learning English as a foreign language. Keywords: Social Media, Learning English, Instagram, Online Learning